Bureaucratic Delegation and Political Institutions : When Are Independent Central Banks Irrelevent? - Keefer, Philip; Stasavage, David (World Bank, Washington, DC, 2014)
The government's ability to credibly commit to policy announcements is critical to the successful implementation of economic policies as diverse as capital taxation and utilities regulation. One frequently advocated means of signaling credible commitment is to delegate authority to an agency that will not have an incentive to opportunistically change policies once the private sector has taken such steps as signing wage contracts or making irreversible investments. Delegating authority is suggested as a government strategy particularly for monetary policy. And existing work on the independence of central banks generally assumes that government decisions to delegate are irrevocable . But delegation - in monetary policy as elsewhere-is inevitably a political choice, and can be reversed, contend the authors. They develop a model of monetary policy that relaxes the assumption that monetary delegation is irreversible. Among the testable predictions of the model are these: A) The presence of an independent central bank should reduce inflation only in the presence of political checks and balances. This effect should be evident in both developing and industrial countries. B) Political actions to interfere with the central bank should be more apparent when there are few checks and balances. C) The effects of checks and balances should be more marked when political decisionmakers are more polarized. The authors test these predictions and find extensive empirical evidence to support each of the observable implications of their model: Central banks are associated with better inflation outcomes in the presence of checks and balances. The turnover of central bank governors is reduced when governors have tenure protection supported by political checks and balances. And the effect of checks and balances is enhanced in more polarized political environments.